A new exposure of the North Curry Sandstone Member (Dunscombe Mudstone Formation, Mercia Mudstone Group: Carnian, Triassic), near Taunton, Somerset (UK): The location of Charles Moore's vertebrate specimens resolved. Issue 6 (December 2022) - Dawson, Garry J.; Burley, Stuart D.; Ruffell, Alastair; Benton, Michael J.; Duffin, Christopher J.
Abstract: There is renewed interest in a series of Carnian-aged sandstone units across the UK because they represent a unique event in the Late Triassic, the Carnian Pluvial Episode (CPE), from 233 to 232 Ma. The North Curry Sandstone Member of the Mercia Mudstone Group in Somerset is of particular importance because it yielded a rich fauna of shark, bony fish and amphibian remains in coarse-grained sandstones to Charles Moore in the 1860s. However, the exact location and age of his important collection had not been identified. Here, we demonstrate that the Moore collection comes from the North Curry Sandstone Member in a location in the village of Ruishton, just east of Taunton, where a new road cutting reveals both the bone-rich units and a complete succession through the CPE, a time of major climatic and biotic upheaval. The 16 m section comprises several sandstones interbedded with red-green mudstones, representing a terrestrial environment with lacustrine, evaporitic mud flat and fluvial deposits.